A membrane fusion protein, Ykt6, regulates epithelial cell migration via microRNA-mediated suppression of Junctional Adhesion Molecule A. Issue 14 (18th July 2018) - Naydenov, Nayden G.; Joshi, Supriya; Feygin, Alex; Saini, Siddharth; Litovchick, Larisa; Ivanov, Andrei I.
ABSTRACT: Vesicle trafficking regulates epithelial cell migration by remodeling matrix adhesions and delivering signaling molecules to the migrating leading edge. Membrane fusion, which is driven by soluble N-ethylmaleimide-sensitive factor associated receptor (SNARE) proteins, is an essential step of vesicle trafficking. Mammalian SNAREs represent a large group of proteins, but few have been implicated in the regulation of cell migration. Ykt6 is a unique SNARE existing in equilibrium between active membrane-bound and inactive cytoplasmic pools, and mediating vesicle trafficking between different intracellular compartments. The biological functions of this protein remain poorly understood. In the present study, we found that Ykt6 acts as a negative regulator of migration and invasion of human prostate epithelial cells. Furthermore, Ykt6 regulates the integrity of epithelial adherens and tight junctions. The observed anti-migratory activity of Ykt6 is mediated by a unique mechanism involving the expressional upregulation of microRNA 145, which selectively decreases the cellular level of Junctional Adhesion Molecule (JAM) A. This decreased JAM-A expression limits the activity of Rap1 and Rac1 small GTPases, thereby attenuating cell spreading and motility. The described novel functions of Ykt6 could be essential for the regulation of epithelial barriers, epithelial repair, and metastatic dissemination of cancer cells.